Changes in Mental Health and Views on Communication and Activities of Public Institutions among Swedes during the COVID-19 Pandemic—A Cross-Sectional Repeated Measures Design - Birgitta Kerstis (MDPI AG, 2021)
Although many studies have been conducted on the effects of COVID-19 on individual lives, only a few focus on the changes in mental health and views of public institutions during the pandemic. This study aimed to investigate how mental health, i.e., life satisfaction, worries, and psychological distress, and views on public institutions’ communication and activities have changed among Swedes during the COVID-19 pandemic, and whether this was moderated by age and sex. In April–May 2020 (survey 1) and in January–February 2021 (survey 2), 2554 adults and 1904 newly recruited adults, respectively, anonymously completed online surveys. We found that life satisfaction and psychological distress did not change from survey 1 to survey 2. However, the level of worries increased, and the positive views of the public institutions decreased. Moreover, worries and psychological distress increased more in young adults than older adults. Finally, the change in the views of the public institutions was not related to the change in worries. Our results highlight the COVID-19 long-term impacts on individual mental health and call for the need for future research concerning the consequences for the population, especially among young adults. The results also indicate that the views on activities of public authorities decreased over time, especially among men. Given that loss of this trust can have vastly negative effects, for instance, on the vaccine campaign, it is important to monitor this trend, to increase awareness among Swedish authorities. The results also stress for institutions to provide adequate support both during the COVID-19 pandemic and in a future crisis.